A New Historicist Reading of Emily Brontë ’s Wuthering Heights - Shilan Abdulrahman Abdulkarim (مجلة الباحث, 2026)
Drawing principally on Michel Foucault’s agency and Stephen Greenblatt’s ideas regarding new historicism, this article focuses on Heathcliff, Nelly, and Catherine in Emily Brontë ’s Wuthering Heights (1847). It reveals how Brontë stands against the ideology of the nineteenth century period in England. It suggests that Brontë implements her agency through the characters of the novel. As a symbol of the lower class, Heathcliff shatters the ideology of class structure in the nineteenth century era. Nelly as a servant, rejects the class, racial and patriarchal ideology of English society. Moreover, Catherine represents anti-practice against the class structure of society. Accordingly, this study offers a new historicist reading of the novel. It argues that there are times when representations of the characters and their relationships could be read as anti-practices, which depicts agency. The findings reveal that the historical context has well left its imprints on this novel. Moreover, hierarchical class and gender discourses and embedded power structures are both supported and questioned.